Sirolimus‐coated balloon versus everolimus‐eluting stent in de novo coronary artery disease: Rationale and design of the TRANSFORM II randomized clinical trial. Issue 4 (2nd September 2022) - Greco, Antonio; Sciahbasi, Alessandro; Abizaid, Alexandre; Mehran, Roxana; Rigattieri, Stefano; de la Torre Hernandez, Jose M.; Alfonso, Fernando; Cortese, Bernardo
Abstract: Background: Percutaneous coronary intervention (PCI) with drug‐eluting stent (DES) implantation is a widely adopted strategy for the treatment of de novo coronary artery disease. DES implantation conveys an inherent risk for short‐ and long‐term complications, including in‐stent restenosis and stent thrombosis. Drug‐coated balloons are emerging as an alternative approach to fulfill the "leaving nothing behind" principle and avoid long‐term DES‐related complications. Design: TRANSFORM II is an investigator‐initiated, multicenter, noninferiority, randomized clinical trial, testing a sirolimus‐coated balloon (SCB) versus the standard of care for native coronary vessels with a 2–3 mm diameter, in terms of 12‐month target lesion failure (TLF; primary endpoint) and net adverse cardiovascular events (coprimary endpoint). Patients undergoing PCI will be randomized to be treated with either SCB or new‐generation everolimus‐eluting stent and will be followed up clinically for up to 60 months. Assuming a TLF rate of 8% at 12 months with DES, a sample size of 1325 patients was chosen to ensure an 80% power to detect a 1.5% lower incidence in the SCB group with a type I error rate of 0.05. The TRANSFORM II trial is registered on clinicaltrials.gov (identification number NCT04893291). Several substudies, including an optical coherence tomography assessment at 9 months (intracoronary imaging substudy), will investigate the study device in different clinical and lesion settings. Conclusions: The randomized TRANSFORM II trial will determine whether a novel SCB is noninferior to a current everolimus‐eluting stent when adopted for the treatment of de novo lesions in coronary vessels with a diameter between 2 and 3 mm.